Nilai-nilai Tauhid dalam Mata Pelajaran Biologi (Telaah pada Mata Pelajaran Biologi) - Yudril Basith (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2021)
This study aims to find the values of tauhid (religion) in biology (science) subjects. This type of research is a qualitative study using an interpretive approach. The main source of the research is the biology textbook for SMA / MA students written by Slamet Prawirohartono. The conclusion of this research is that someone who studies biology will be able to get an understanding of monotheism (religion). This can be seen from the value of monotheism contained in the subject of biology, which is tawhid rububiyah that mean the god is the only one can control and creator universe. Someone can develop his potention to maintain and preserve the universe as a form of worship to God. Second, uluhiyah, this is in the form of the tasbih of the universe in the form of the order and balance of the universe that Allah created for every creature, three Asma 'wa sifah, this is the form of Allah's affection for every creature that He has created. This can be seen from biological materials such as material on scientific methods that recommend utilizing the five senses in studying ancient verses, biodiversity as a gift of God's beauty, ecology which is the unity and harmony of God's creation in order to maintain the balance of the environment (ecosystem)